The Role of Comparisons in Judgments of Loneliness - Arnold, Andrew J.; Kappes, Heather Barry; Klinenberg, Eric; Winkielman, Piotr (Frontiers in Psychology, 2021)
Loneliness—perceived social isolation—is defined as a discrepancy between existing social relationships and desired quality of relationships. Whereas most research has focused on existing relationships, we consider the standards against which people compare them. Participants who made downward social or temporal comparisons that depicted their contact with others as better (compared to other people’s contact or compared to the past) reported less loneliness than participants who made upward comparisons that depicted their contact with others as worse (Study 1-3). Extending these causal results, in a survey of British adults, upward social comparisons predicted current loneliness, even when controlling for loneliness at a previous point in time (Study 4). Finally, content analyses of interviews with American adults who lived alone showed that social and temporal comparisons about contact with others were both prevalent and linked to expressed loneliness (Study 5). These findings contribute to understanding the social cognition of loneliness, extend the effects of comparisons about social connection to the important public health problem of loneliness, and provide a novel tool for acutely manipulating loneliness.